Hubungan Prostate Volume dan Intravesical Prostatic Protrusion terhadap International Prostate Symptom Score pada Pasien Benign Prostate Hyperplasia (Relationship between Prostate Volume and Intravesical Prostatic Protrusion and International Prostate - Rahma Illa Putri Utami; Septa Surya Wahyudi; Yuli Hermansyah (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Diagnosis of benign prostate hyperplasia (BPH) can be established through transabdominal ultrasonography (TAUS), a noninvasive supportive examination which measure prostate volume (PV), and intravesical prostatic protrusion (IPP). The severity of obstructive symptoms experienced by the patient was assessed by international prostate symptom score (IPSS) questionnaire. This study aimed to analyse the relationship between both PV and IPP and IPSS in BPH patients. This was an observational analytic study with cross sectional design conducted at Department of Urology Surgery Bina Sehat Hospital Jember, Paru Hospital Jember and Bhayangkara Hospital Bondowoso during October-November 2016 in 30 respondents. The average of PV was 52.01±25.18 mL, IPP was 12.67±6.69 mm and IPSS score was 25.60±9.20. The results of Spearman correlation between the PV and Voiding-IPSS, Storage-IPSS, or total score IPSS and IPP and Voiding IPSS showed no significant correlation (p =0.319; p=0.067; p=0.085; p=0.183). Spearman correlation between the IPP and Storage-IPSS or total score IPSS resulted p value equal to 0.012 and r=0.451 and p=0.027 and r=0.404, which showed a significant correlation with moderate correlation strength. Statistically, IPP correlated to IPSS score better than PV. Keywords: BPH, international prostate symptom score, transabdominal ultrasonography